Recent Advances in the Carbon–Carbon Bond-Forming Reactions of N-Acylketimines - Asahara, Haruyasu (Synthesis, 2017)
N-Acylketimines are important synthetic building blocks used in the synthesis of a wide variety of functional amino compounds including cyclic and acyclic products. This review focuses on carbon–carbon bond-forming reactions of N-acylketimines to construct amino compounds having tetrasubstituted carbon centers.1 Introduction2 Preparation of N-Acylketimines2.1 Nucleophilic Addition of Amide Derivatives2.2 Acylation of Imine Derivatives2.3 An Aza-Wittig-Type Reaction2.4 Oxidation of Amine Precursors3 Reactions of N-Acylketimines3.1 Cyclic Ketimines3.2 Acyclic Ketimines4 Conclusions
Keywords: N-acylketimine; C–C bond-forming; nucleophilic addition; electrophilicity; asymmetric synthesis